IMPLIKATUR PADA FILM 700 DAYS OF BATTLE US VS THE POLICE (Bokutachi to Chuuzai San no Shichi Nichi Sensou) - Dimas Anugrah; Arza Aibonotika; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to describe out the implicatures of a conversation of a group of high school teenagers who are at war with police officer told in the film 700 Days Of Battle Us Vs The Police. This study is using theory put forward on Grice (1975) theory of conversational implicatures to analyze the prescribed conversations with the maxim offense on the Principle of Cooperation. The results of this study are 22 data that Violate Cooperation Principle. Such violations include 2 Maxim of Quantity, 4 Maxim of Quality, 6 Maxim of Relevance or Relationship Offenses and 14 Maxim of Manner. It’s generally known the the purpose of violation of the Principle of Cooperation to maintain the compassionate benefit in the conversation.Keywords: Implicature, Maxim, Violation Of The Principle Of Cooperation.